An improved experimental method for local clothing ventilation measurement - Ying Ke; Jun Li; George Havenith (2014)
A clothing local ventilation measuring device based on the Lotens-Havenith steady state tracer gas method was developed and an improved experimental method for understanding local ventilation mechanisms was proposed. The local ventilation system can measure the arm, chest and back ventilation rates at the same time. Local ventilation mechanisms of an impermeable garment at two activities (static, walking) and two wind speeds (no wind, 1.2m/s) were studied, with a focus on determining the pathways of ventilation through the different garment openings. The results showed that local ventilation rates of chest, back and arm varied considerably over locations and conditions. As expected, ventilation rates were highest for all locations at walking with wind conditions. Ventilation mechanism changed at different walking and wind conditions. The main air exchange pathway for all locations was through the garment bottom. Wind had a greater impact on clothing local ventilation than walking. Relevance to industry: Clothing ventilation impacts worker's thermal comfort and safety directly both in the cold and heat. The new clothing local ventilation measuring device developed in this paper can measure both clothing local and whole ventilation. It can also help us to separate the different pathways for heat loss through clothing.© 2013 Elsevier B.V.